The Effect of Tax Sanctions and Tax Knowledge on Individual Taxpayer Compliance With Tax Morals As a Moderation Variable - Annisa Ramadhani Putri; Muhammad Nur; Kumba Digdowiseiso (Jurnal Syntax Transformation, 2024)
This study aims to analyze the Effect of Tax Sanctions and Tax Knowledge on Individual Taxpayer Compliance with Tax Morals as a moderating variable (Empirical Study at KPP Pratama Jakarta Cakung Year 2018-2022). The method of determining the sample in this study is the convenience sampling method. In this study, the number of samples used was 100 respondents, the data was processed using the Structural Equation Model (SEM) method using WarpPLS version 7.0 software. The results of this study indicate that (1) tax sanctions have a significant positive effect on individual taxpayer compliance (2) tax knowledge has a significant positive effect on individual taxpayer compliance (3) tax morale cannot moderate the effect of tax sanctions on individual taxpayer compliance (4) tax morale can moderate tax knowledge on individual taxpayer compliance.